2000
DOI: 10.1021/ic990784l
|View full text |Cite
|
Sign up to set email alerts
|

NMR and EPR Investigations of Iron Corrolates:  Iron(III) Corrolate π Cation Radicals or Iron(IV) Corrolates?

Abstract: The chloroiron corrolates of 2,3,7,8,12,13,17,18-octamethyl- and 7,13-dimethyl-2,3,8,12,17,18-hexaethylcorrole ([(Me8C)FeCl] and [(7,13-Me2Et6C)FeCl], respectively) and their bisimidazole complexes have been investigated by NMR spectroscopy as a function of temperature, and by EPR spectroscopy at 4.2 K. Magnetic susceptibilities were measured by the modified Evans method. It is found that the electron configuration of the chloroiron corrolates is that of a S = 3/2 Fe(III) center coupled to a corrolate pi radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
101
1
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 51 publications
21
101
1
1
Order By: Relevance
“…4 This orbital has large π spin density at the meso-carbon positions and negligible spin density at the pyrrole -carbons. 4,79,82 We have recently published a detailed study 10 that fully corroborates the earlier interpretations of the NMR data for the chloroiron octaalkylcorrolates, 79 in which several experimental techniques (magnetic susceptibility measurements, Mössbauer, and NMR spectroscopy), as well as DFT calculations, were used to establish unambiguously the electron configuration and spin density distributions of the chloroiron octaalkyl-and triphenylcorrolates, as well as the phenyliron octaalkylcorrolate. 10 In all of the chloroiron complexes, the NMR spectra were strongly indicative of an electron configuration in which the metal is S ) 3 / 2 Fe(III) and the corrolate macrocycle is a cation radical, Corr 2-• .…”
Section: The Special Case Of Iron Corrolatessupporting
confidence: 61%
See 2 more Smart Citations
“…4 This orbital has large π spin density at the meso-carbon positions and negligible spin density at the pyrrole -carbons. 4,79,82 We have recently published a detailed study 10 that fully corroborates the earlier interpretations of the NMR data for the chloroiron octaalkylcorrolates, 79 in which several experimental techniques (magnetic susceptibility measurements, Mössbauer, and NMR spectroscopy), as well as DFT calculations, were used to establish unambiguously the electron configuration and spin density distributions of the chloroiron octaalkyl-and triphenylcorrolates, as well as the phenyliron octaalkylcorrolate. 10 In all of the chloroiron complexes, the NMR spectra were strongly indicative of an electron configuration in which the metal is S ) 3 / 2 Fe(III) and the corrolate macrocycle is a cation radical, Corr 2-• .…”
Section: The Special Case Of Iron Corrolatessupporting
confidence: 61%
“…80 We have also recently reported the investigation of a series of chloroiron triphenylcorrolates by 1 H and 19 F NMR spectroscopy; 81 the 1 H NMR spectra of several chloroiron triphenylcorrolates have also been reported by Ghosh and coworkers. 9 The results of all of these studies have shown unambiguously that these five-and six-coordinate iron corrolates are actually iron(III) corrolate(2-•) π cation radicals, 79,80 and that axial ligands such as cyanide can readily autoreduce the corrolate radical, leaving a low-spin Fe(III) mono(cyanide) complex. 80 The nature of the magnetic coupling between the unpaired electrons on the metal and the corrolate(2-•) π cation radical differs, depending on the axial ligand(s) present: Very strong antiferromagnetic coupling is observed in the case of the chloride complexes (as evidenced by the fact that the meso-H resonances are found at +187(1) and +174(2) ppm at 300 K, which can only occur when there is large negatiVe spin density at the meso-carbons, as shown in Figure 9f, to the point of the C m position).…”
Section: The Special Case Of Iron Corrolatesmentioning
confidence: 97%
See 1 more Smart Citation
“…The oxidation and reduction of these complexes (Table 1, entries 6, 7) were shown to be corrole-and metal-centered, respectively, which also led to isolation of an authentic iron(IV) corrole cation radical [37]. Still, the interpretations regarding the iron(IV) oxidation state were recently challenged via NMR analysis of (omc)Fe(Cl) and these authors propose that the alternative formulation of iron(III) corrole cation radical cannot be ruled out [38]. The intriguing demonstration that (tpfc)Fe(Cl) is a good oxidation catalyst [10] initiated the full characterization of this and other related iron complexes [20,39].…”
mentioning
confidence: 99%
“…Subsequently, Gross and co-workers developed the coordination chemistry of meso-tris(pentafluorophenyl)corrole extensively [105] and used some of the complexes as catalysts for oxygen-atom transfer, [106][107][108] cyclopropanation, [107] and other reactions. Our laboratory [109,110] and that of Walker [111][112][113] have studied the description of the electronic structure of high-valent transition-metal corroles, a key finding being that corroles often act as highly noninnocent ligands. [114][115][116] …”
Section: Angewandte Chemiementioning
confidence: 99%